Adolescent Males and Firesetting: An Interpretative Phenomenological Analysis. Issue 1 (2nd January 2016) - Reilly, Claire; Johnson, Dan
ABSTRACT: Adolescent firesetting is costly and potentially fatal but relatively little is known about the behavior, particularly from the perspective of those engaging in it. The literature has previously focused on prevalence or theoretical frameworks but there is a paucity of research on young people's experience and the meaning they attribute to the behavior. Developing a greater understanding of this can inform theory development and intervention programs. Data was gathered from semi-structured interviews of adolescent boys residing in secure care. Interpretative Phenomenological Analysis was used to elicit key themes within the data. The analysis highlighted three super-ordinate themes of Fire as Function, Function determines Acceptability, and Function determines Severity. These themes suggest the young people within this group perceive the function of the fire as imperative over the physical properties of fire. They described the many functions of firesetting and related their view that firesetting is pathological in the absence of function. Exploring young people's experience of firesetting has provided an insight into the function of the behavior for them and the relation of this function to the precepts they apply. This understanding will help design quantitative nomothetic research and provide clinicians with areas to explore within assessment and intervention.